Vitamin D levels and Vitamin D-related gene polymorphisms in Chinese children with type 1 diabetes - Chen, Xiaofang; Fu, Jia; Qian, Ying; Zhi, Xiufang; Pu, Linjie; Gu, Chunyu; Shu, Jianbo; Lv, Ling; Cai, Chunquan (Frontiers in Pediatrics, 2022)
Low vitamin D levels may play a role in type 1 diabetes(T1D) susceptibility. Since 25(OH)D synthesis is genetically regulated, single nucleotide polymorphisms (SNPs) of important genes have also been shown to modulate the risk of T1D, so this study aimed to investigate the relationship between five SNPs in CYP2R1, DHCR7, CYP24A1, VDR genes, serum 25(OH)D levels and T1D in Chinese children. This case-control study included 141 T1D patients and 200 age-matched healthy children.25 (OH) D concentration was determined, genotyping was performed by High resolution melting (HRM). There was a significant difference in the prevalence of vitamin D deficiency, insufficiency, and sufficiency between T1D and healthy controls. (2 =9.80, p=0.008) , however no evidence of the association between any group of SNPs and circulating 25(OH)D levels was observed. The allele distribution of CYP2R1(rs1993116) was significantly different between T1D and control group (P =0.040), and the C allele carriers of rs1993116 had a higher risk of T1D than the T allele carriers, Carriers of the CC and CT genotypes of rs1993116 have higher T1D risk than those carrying the TT genotype. GMDR analysis revealed a significant interaction between CYP2R1(rs12794714) and CYP2R1(rs1993116) in the risk of T1D with a maximum testing balance accuracy of 60.39 %.